Unemployment and Labor Force Participation in Turkey - Aysit Tansel; Zeynel Abidin Ozdemir; Emre Aksoy (Institute for the Study of Labor (IZA), 2015)
This paper investigates the relationship between labor force participation rate and unemployment rate in Turkey a developing country. Cointegration analysis is carried out for the aggregate and gender and age specific series. The findings indicate that there is no long-run relationship between labor force participation and unemployment rates in Turkey. Thus, unlike in the case of the developed countries the unemployment invariance hypothesis is supported in Turkey.
Keywords: E24; 330; unemployment invariance hypothesis; cointegration; Turkey